2020
DOI: 10.1038/s41598-020-75885-x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic heat stress regulates the relation between heat shock protein and immunity in broiler small intestine

Abstract: Chronic heat stress is considered to decrease the immune functions which makes negative effect on broiler growth performance. Here, we investigated the relationship between chronic heat stress, growth performance, and immunity in the small intestine of broilers. The study included two groups (control and heat stressed group) with eight replications per group. Ten broilers of 20-day aged were allocated in each replication. On day 35, the treatment group was subdivided into two groups based on their body weights… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 70 publications
1
40
0
Order By: Relevance
“…It was reported that the HSP-70 protein expression was significantly increased in different broiler breeds subjected to chronic heat stress with severe inflammation damage of the brain, muscle, and heart tissues [2]. HSP-70 was found to be associated with pro-inflammatory cytokine levels (i.e., TNF-α) in broilers subjected to chronic heat stress [49]. He, Yu, He, Hu, Xia and He [10] reported an increase in the mRNA abundances of HSP-70 in the spleen of heat-stressed yellow-feather broilers associated with increased TNF-α among other pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the HSP-70 protein expression was significantly increased in different broiler breeds subjected to chronic heat stress with severe inflammation damage of the brain, muscle, and heart tissues [2]. HSP-70 was found to be associated with pro-inflammatory cytokine levels (i.e., TNF-α) in broilers subjected to chronic heat stress [49]. He, Yu, He, Hu, Xia and He [10] reported an increase in the mRNA abundances of HSP-70 in the spleen of heat-stressed yellow-feather broilers associated with increased TNF-α among other pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of environmental or metabolic stress exposure induces over-expression of HSPs in order to protect cells from damage [49][50][51]. It was reported that the HSP-70 protein expression was significantly increased in different broiler breeds subjected to chronic heat stress with severe inflammation damage of the brain, muscle, and heart tissues [2].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that HS-induced up-regulation of Occludin expression in Caco-2 cells is mediated by activation of heat shock factor-1(HSF-1), which can promote the expression of HSPs [ 37 ]. In addition, HS exposure results in the overexpression of HSPs in organs of different species [ 7 , 38 42 ]. Moreover, HSPs expression in the intestine were considered to be more sensitive to long-term stress than conventional stress markers such as serum concentrations of catecholamines, cortisol, lactate [ 38 ], and showed significant associations with intestinal immunity [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has demonstrated a strong correlation between oxidative stress, growth performance, and metabolic disorders (34). High-intensity HS induces intestinal ischemia, as well as autolysis and sloughing the intestinal villi, leading to impairments of intestinal morphology, or reduction of antioxidant enzyme activities (35,36). Misregulation in this ROS-scavenging process leads to the generation of excessive amounts of ROS, it can damage lipids, proteins, and DNA, which is associated with changes in mitochondrial functions (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%